Leadership and Role Modelling Understanding Workplace Dynamics (Palgrave Studies in Leadership and Followership,, 2018)
'Understanding the dynamics of role modelling is an essential part of fostering a developmental culture at work or school. This book is packed with important information and insights based on cases and examples from various professional and cultural contexts, especially for those who want to make their places of work or study an enriching environment that affords positive transformative experiences.' -Aarti Ramaswami, Academic Director and Associate Professor of Management, ESSEC Business School Asia-Pacific, Singapore This edited volume explores the influence of role modelling as a process in the workplace; in particular, whether it can aid career development, offer psycho-social support, and provide the motivation and means to achieve goals. Chapters examine whether the dynamics of personal identification and self-belief can affect the way that role models are chosen, placing emphasis on geographical diversity and cultural aspects. By including studies of gender and followership in both American and Indian settings, the scholars and practitioners who contribute to this collection outline key aspects of role modelling, and its effect as a developmental tool in the workplace, from the perspective of the individual and organisations. This book is a valuable resource for academics interested in organisations, management, and diversity, as well as practitioners and policy-makers involved in leadership programmes, who will find its collection of both theoretical and empirical findings extremely useful.